Obesity is associated with IL-6 gene polymorphisms rs1800795 and rs1800796 but not SOCS3 rs4969170 - ULUCAN, KORKUT (My University, 2023)
Background: An imbalance of inflammatory factors can stimulate obesity by inducing chronic inflammation in adipose tissue. Interleukin-6 (IL-6) is a cytokine with both inflammatory and anti-inflammatory functions. Suppressor of cytokine signaling 3 (SOCS3) acts as an inhibitor for a number of cytokine signals. The IL-6 and SOCS3 genes are known to be involved in lipid and energy metabolism, although it is unclear how these genes relate to obesity. The aim of this study is to determine whether the obesity risk is associated with the IL-6 (rs1800795, rs1800796) and SOCS3 (rs4969170) gene polymorphisms. Methods and results: Based on their body mass index (BMI) scores, 185 people were determined, of whom 90 were from the control group and 95 were obese. Anthropometric measurements and biochemical parameters of the study subjects were documented during the examination. Genomic DNA isolation was performed from the blood samples of all participants. IL-6 (rs1800795, rs1800796) and SOCS3 (rs4969170) polymorphisms were detected by real-time quantitative polymerase chain reaction (qRT-PCR) from genomic DNA samples. The IL-6 rs1800795 and rs1800796 variants showed a significant difference between the control and obese groups (p = 0.027; p = 0.013). The SOCS3 rs4969170 variation did not substantially differ between the control and obese groups (p = 0.825). Conclusion: In our study, IL-6 rs1800795(G/C) and rs1800796(G/C) polymorphisms appeared to be a risk factor for obesity. The C allele was associated with the obesity phenotypes. However, the SOCS3 rs4969170 (A/G) polymorphism was not linked to an increased risk of obesity. IL-6 polymorphisms may be new targets for obesity treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; GENETICS & HEREDITY; Moleküler Biyoloji; Genetik; Molecular Biology; Genetics; IL-6; SOCS3; Obesity; Polymorphism; INTERLEUKIN-6; INFLAMMATION; ENERGY